Torsional repair of damaged single-box multi-cell composite box-girder with corrugated steel webs using CFRP. Part II: Theoretical investigation. (1st December 2022) - Zhu, Yingbo; Shen, Kongjian; Fascetti, Alessandro; Wan, Shui; Brigham, John C.; Fu, Jundong
Highlights: A rotating-angle model for predicting the torsional behavior of CFRP-repaired SBMC-CBGCSW. FRP used as reinforcement is incorporated in equilibrium of concrete elements. Constitutive laws for the softened and FRP-confined damaged concrete and the buckled steel web are proposed. Three-stage average stress–strain relationships for concrete struts are developed; Rational shear strain relationship between CSWs for predicting the torsional behavior of inner CSWs. Abstract: Due to their low torsional stiffness, Single-Box Multi-Cell Composite Box-Girders with Corrugated Steel Webs (SBMC-CBGCSWs) under eccentric load are more prone to fail when compared to traditional concrete structures, leading to the increased probability of the need of repair during their life span. To avoid secondary failures and provide a theoretical basis for the evaluation of the optimal repair scheme, a rational rotating-angle model is proposed in this paper to predict the torsional response of damaged SBMC-CBGCSWs repaired with FRP. This proposed model primarily incorporates the effect of FRP on the damaged concrete and proposes constitutive models for the FRP-repaired concrete. At the same time, the effective thickness of shear flow zone for concrete slabs is considered, and the three-stage average stress–strain relationships for concrete struts are proposed for this model. Besides, a new shear strain relationship between inner and outside Corrugated Steel Webs (CSWs) is adopted to estimate the torsional behavior of inner CSWs in SBMC-CBGCSW. The comparison of theoretical predictions and experimental results presented in the companion paper in terms of torque-twist curves, key points, and strains in FRP strips, concrete slabs and CSWs indicates that the proposed model can accurately predict the entire nonlinear behavior of the damaged SBMC-CBGCSWs repaired using CFRP. The parametric study carried out by this proposed model shows that the ultimate strength of CFRP-repaired SBMC-CBGCSWs is approximately linear with the damage coefficient of concrete and the CFRP ratio. In addition, it is found that the effective thickness of shear flow zone and the three-stage average stress–strain relationships for concrete struts adopted in this model can produce reliable predictions of cracking and ultimate torques.